Socio Economic Profile and Nutritional Status of the Rickshaw Pullers of Dhaka City Along with their Energy Intake Gap - Tasnima Mahjabin; Ahmed Jubayer; Islam Md. Hafizul; Kazi Abul Kalam; Abira Nowar; Khan Md. Nazrul Islam (International Journal of Nutrition, 2021)
Background This study focused on nutritional status of the rickshaw pullers, their dietary energy and nutrients consumption along with their energy intake gap as compared to expenditure. Methods A cross sectional study was carried out at 15 different important locations of Dhaka city during December-January 2018. In total, 670 rickshaw pullers from these locations were randomly selected. Printed predesigned and validated semi structured questionnaire was used to record necessary information. Nutritional status was determined according to Asia specific BMI cut- off values. Energy expenditure was calculated using their Basal Metabolic Rate (BMR) and Physical Activity Level (PAL) value. 24-hour dietary recall method was administered for dietary analysis. Results About 65.4% of them were found within normal BMI range. About 11.5% were underweight and about 23.1% were found having more than normal BMI. Percentage of both underweight (39.0%) and overweight (35.8%) were found higher among those who were between 25 and 35 years. Average daily dietary energy consumption was 2391 kcal and energy expenditure were found 4608 kcal. Their energy consumption was found 2217 kcal less compared to their energy expenditure. Conclusion The current study revealed the nutritional status, dietary intake of the rickshaw pullers of Dhaka city and found energy gap in their dietary intake compared to their expenditure. For their better health and nutrition outcome integrated approach should be taken by the responsible authorities.
Keywords: Nutritional status